Talleres de las conciencias lingüísticas para el desarrollo del lenguaje para niños de 4 a 5 años - De la Cruz Llango, Jenifer Fernanda (2022)
This project designs and develops several workshops based on linguistic awareness in order to develop an effective language in the children of the Educational Unit ¨ Pujilí ¨ between the ages of 4 to 5 years. The educational unit is located in the province of Cotopaxi, in the Pujilí canton, Pujilí parish, Chimbacalle neighborhood. Considering the great importance of the project for the educational sector, especially for infants of initial two, its purpose is to correct or mitigate the problems of oral language development in infants of these ages, a problem that has been investigated in a previous project carried out by Suquilanda and Chuqui in March 2022, which mention that; The problem of the children of the "Pujilí" Educational Unit is the deficiency in oral communication due to various scenarios such as: physical and verbal aggression, delay in intellectual development, poor stimulation of speech, stuttering, they cannot pronounce words correctly. They through the literary, bibliographic review and a previous relevant analysis determine that; The lack of language development in children is due to the ignorance and application of linguistic awareness by teachers, as well as the lack of support from parents or legal guardians that prevent the participation of infants in an active way. . The workshops consist of quality and validity, since they have been thoroughly evaluated by specialist academics, they are framed in four determinants such as; phonological awareness, lexical awareness, semantic awareness, and syntactic awareness.